The global economy, in a downturn; corporate social responsibility, at the crossroads - Knowledge@SMU (Institutional Knowledge at Singapore Management University, 2009)
While plenty of misconception still exists, the concept of corporate social responsibility (CSR) has been gaining traction, and many companies, especially the larger corporations, have been implementing their own programmes in this field. Just as when a growing number of companies are treating CSR as an integral part of what they do, the economic crisis struck, threatening to derail many of these fledging efforts. Going forward, CSR needs to be seen as more than just philanthropic activities if they are to continue in a meaningful way, says CSR expert Peter Shergold.